A guest for a day? An analysis of Uzbek 'language migration' into the Japanese educational and labour markets. Issue 3 (3rd July 2021) - Dadabaev, Timur; Sonoda, Shigeto; Soipov, Jasur
ABSTRACT: By elaborating on the findings of two data sets collected in both Uzbekistan and Japan, this paper demonstrates that Japan has increasingly become a new frontier for Uzbek youngsters who use educational opportunities to seek temporary employment. This attitude of Uzbek students in Japan, which relates to their predisposition towards 'work' rather than 'study', can be explained by several factors. One set of explanations relates to their commitment to link their future with a home country due to the expectations of their families and communities. Another, at least partially, relates to the ambiguous and unsettled image of the role of Japan for their future, which might be contributing to their study–work imbalance.